Prospective study on the dose relationship of mitomycin C–induced interstitial pneumonitis - Jaap Verweij; Thea van Zanten; Tjeu Souren; Richard P. Golding; Herbert M. Pinedo (1987)
Lung damage after mitomycin C (MMC) was first reported in 1978. Although this side effect has been frequently reported since then, there are no data on dose dependency nor on incidence. Therefore, the authors initiated a prospective study to obtain more data on this subject. Forty-four patients treated with MMC entered the study; 37 were evaluable. All patients were subjected to repeated physical examinations, chest x-rays, chest computed tomography (CT) scan and pulmonary function tests. The results were evaluated per cumulative dose level. None of the patients had clinical pulmonary toxicity develop; one patient had pulmonary changes on CT scan, the significance of which remained unclarified. The world literature on this subject was also reviewed. Based on the combined data of the present study as well as the literature review, the authors concluded that MMC-related lung toxicity is a dose-dependent side effect, occurring at cumulative dose levels of 20 mg/m2 or more. The incidence is likely to be less than 10%.